(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Objective: To study the characteristic features of sleep disorders specific to patients with arterial hypertension. Material and methods: Research and approaches: As part of our analysis, a main group of 42 participants was formed, including 20 women and 22 men aged 59 to 74 years with established diagnoses of chronic cerebrovascular diseases and hypertension. The control group (CG) consisted of 24 healthy volunteers, including 14 women and 10 men of average age of about 50 years. To assess sleep disorders, both a subjective method - a questionnaire on sleep quality, and objective data from a polysomnographic study were used. Results: The studies showed that 97% of patients with arterial hypertension complained of problems with night sleep. Disturbances in all aspects of sleep structure were recorded, including a significant increase in the time required to fall asleep (33.5±7.7 min), as well as more pronounced wakefulness during sleep (20.1±6.9%), compared with the control group (p<0.01). No serious respiratory disorders during sleep were detected in the grouped patients. A statistically significant reduction in the total duration of sleep (375±71 min) and its efficiency index (80.7±19.2) was also observed. In the control group, the apnea index was 17.1±9.8 versus 5.3±1.4 (p<0.001). The oxygen saturation level was 84.2±1.4% in patients of the main groups and 96.4±1.1% in the control group (p<0.05). Conclusion. In patients with arterial hypertension, there is a connection between sleep disorders characterized by psychophysiological insomnia and the intensity of the vegetative syndrome, as well as the severity of the underlying disease.